Turkey : Non-Bank Financial Institutions and Capital Markets Report - World Bank (Washington, DC, 2013)
Longstanding macroeconomic instability, and inflation in Turkey, have discouraged investment in financial assets, and a persistently high public sector borrowing requirement has crowded funding for the private sector. Notwithstanding, the Government's ongoing stabilization, and structural reforms, are improving the prospects for the development of financial services, though a series of policy issues should be addressed. This study identifies such issues, and formulates recommendations to better address them. Chapter I outlines the advantages of a broad based, diversified financial services industry, lays out the evidence of a clear correlation between financial system development, and per capita income, and, analyzes the outlook for such financial services industry over the next five years. Chapter II, in addressing the mobilization of savings, describes the extent to which macroeconomic uncertainty, chronically high inflation, and ill-suited tax policies have driven significant savings into real estate, gold, and overseas bank accounts. Recommendations suggest the development of a tax system that creates a level-playing field for investment assets, encouraging investments in longer-term/risk-based instruments, among others. Building an institutional investor base is addressed in Chapter III, where key issues are identified for developing the insurance, private pension and mutual fund industries. Chapters IV, V, and VI describe current developments of the equity, debt and derivatives markets, focusing on best practices to further develop venture capital, and, how to strengthen, and improve corporate governance, accounting and auditing standards. Finally, the need to rationalize the atomized oversight structure is recommended, where regulatory agencies should be responsible for supervising an increasingly integrated financial services industry, in addition to considerations on developing a holding company regime for financial, and mixed conglomerates.